Electrophoretic deposition of Mn1.5Co1.5O4 on metallic interconnect and interaction with glass-ceramic sealant for solid oxide fuel cells application - Smeacetto, Federico; De Miranda, Auristela; Cabanas Polo, Sandra; Molin, Sebastian; Boccaccini, Dino; Salvo, Milena; Boccaccini, Aldo R. (Journal of Power Sources, 2015)
Cr-containing stainless steels are widely used as metallic interconnects for SOFCs. Volatile Cr-containing species, which originate from the oxide formed on steel, can poison the cathode material and subsequently cause degradation in the SOFC stack. MnCoO spinel is one of the most promising coating materials due to its high electrical conductivity, good CTE match with the stainless steel substrate and an excellent chromium retention capability. In this work MnCoO spinel coatings are deposited on Crofer22APU substrates by cathodic electrophoretic deposition (EPD) followed by sintering at 800-1150 °C in different atmospheres. Dense, continuous and crack free MnCoO coatings (with thickness ranging from 10 to 40 μm) are obtained on Crofer22APU substrates. Moreover, electrical properties of the coated Crofer22APU alloy are tested up to 2500 h and an excellent compatibility is found between MnCoO coated Crofer22APU and a new glass-ceramic sealant, after 500 h of thermal tests in air, thus suggesting that the spinel protection layer can effectively act as a barrier to outward diffusion of Cr.
Keywords: Area specific resistance; Coating; EPD; Glass-based sealant; SOFC